Penerapan Manajemen Pengelolaan Usaha Dan Strategi Digital Marketing Guna Meningkatkan Penjualan Dalam Era Society 5.0 - Hari Stiawan; Syarifudin Syarifudin; Syamsul Asmedi; Fitria Eka Ningsih; Siti Mundiroh (Universitas Pamulang, 2021)
The Covid-19 pandemic has been going on for 1 year and it is certain that many aspects of people's lives have an impact, especially on business development. Entrepreneurs who are engaged in the UMKM sector are among the ones most affected by this pandemic. They are no longer thinking of expanding their business, but maintaining the business feels difficult. Not a few UMKM actors ended up going bankrupt because they were no longer able to run their business due to losses for quite a long time during this pandemic. One of the efforts that can be made to prevent UMKM businesses from breaking down is by providing education and socialization on strategies to increase turnover or sales. One of the strategies that can be used is digital marketing which can be done easily, cheaply, effectively and efficiently. Digital marketing itself is a strategy for developing products through social media pages, websites, blogs, etc. that use the internet network. The PKM team chose this strategy because it felt that this strategy was very suitable for use in a time when people had to stay at home and use gadgets to access information a lot. By taking advantage of existing opportunities, it is felt that digital marketing will greatly help entrepreneurs to maintain their businesses and increase their sales.